Body: deep inner space (Revista de Ensino em Artes, Moda e Design, 2024)
I seek to bring the darkness of human beings to light. I pursue the depth of the identity, mystery and unconscious, of desire and dreams. This is the approach to all my work, from installations to videos and drawings, and I do it through symbols, some of which return frequently, in different works, years apart; like the circle and circularity, the sailboat, the house, they are all linked by the same content. The house is a natural refuge, the intimate home, it is the mysterious cave of our deepest being. The circle is the circular refuge where the image of the womb resides; the maternal niche, where we find the navel of the earth. The boat is an aquatic dwelling, the cradle of the living, therefore it is linked to the circular refuge of the return to the mother, to the navel of the earth, it is, therefore, a deep cavity; container and content. We really look for ourselves in our unconscious, which is why I try to give a language to nighttime thoughts and bring them to light. The body is then home-space-unconscious-time and time is linked to memory. With pins I write a diary of experimental sign of solitude. Between it and the drawing there is a comparative metamorphosis in which the material represents the human condition, mystical, painful, but also hope, given its relationship with light. They become traces of signs, emergences of brilliance, sometimes they draw maps. All of this becomes an unspeakable condition, typical of the human soul, always related to the dark and obscurity, felt as an internal space of oneself, a desire for healing.
Keywords: body; home-space-unconscious-time; light; drawing; cure